Channel changes downstream of the Hapcheon re-regulation Dam in South Korea - Shin, Young Ho, author; Julien, Pierre Y., advisor; Watson, Chester C., committee member; Wohl, Ellen E., committee member; Grigg, Neil S., committee member (Colorado State University. Libraries, 2007)
The Hwang River is a tributary of the Nakdong River and it covers a drainage area of 1,329 km2 in South Korea. The Hapcheon Main Dam and re-regulation Dam, located 6.5 km downstream of the main dam, were completed in 1989. The purpose of the lower dam is to regulate the downstream flows of the daily three-hour peak hydro power generation at the main power station. The study reach is 45 km long from the Hapcheon re-regulation Dam to the confluence with the Nakdong River. As almost 20 years passed since the Hapcheon Dam was completed, it seems important to monitor the river changes downstream of the dam. The Hwang River has experienced channel adjustments such as changes in channel width, bed material sizes, vegetation expansion, and island formation after the construction of the two dams. These channel changes were caused by changes in flow regime and sediment transport after dam construction. Based on reservoir sediment deposition in 2002, the Hapcheon Main Dam trapped approximately 600,000 m3 of sediment per year since the completion of the dam in 1989. The two dams also dramatically reduced annual peak flows from 654.7 m3/s to 126.3 m3/s (19.3 % of pre-dam condition). The main objectives of this study are as follows; · Identify past spatial and temporal trends and the corresponding response of the channel before and after dam construction. · Analyze and predict future channel changes in lateral and vertical variations such as channel width, bed slope, bed material, and expansion of islands and vegetation. · Analyze and evaluate the channel changes due to flow pulses by the operation of the Hapcheon Re-regulation Dam. An analysis of a time series of aerial photographs taken in 1982, 1993, and 2004 showed that the non-vegetated active channel width narrowed an average of 152 m (47 % width reduction since 1982). Also, the non-vegetated active channel area decreased an average of 6.6 km2 (44 % reduction since 1982) between 1982 and 2004, with most changes occurring after dam construction. The average median bed material size increased from 1.07 mm in 1983 to 5.72 mm in 2003, and the bed slope of the reach decreased from 0.000943 in 1983 to 0.000847 in 2003. The riverbed vertical degradation is approximately 2.6 m for a distance of 15 km below the re-regulation dam. Since the dam construction, the channel moved toward a new stable/equilibrium condition. The analysis of aerial photographs and field surveys shows that the 2004 channel width was on average 1.5 times greater than the estimated equilibrium width from the Julien and Wargadalam (1995) hydraulic geometry equations. It is expected from the result of GSTAR-1D steady simulations that the thalweg elevation will reach a stable condition around 2013-2015, 25 years after the dam construction in 1989. Although the Hapcheon Re-regulation Dam attenuated peak flows, there are daily flow pulses due to peak hydropower generation and sudden sluice gate opening and closing during flood seasons. The effects of these pulses of water level and discharge downstream of the re-regulation dam are analyzed using the unsteady sediment transport numerical model (GSTAR-1D). The daily pulses and flood peaks exert a greater impact on downstream channel geometry than steady discharge conditions. The sediment transport rates (tons/day) of daily pulses and flood peaks were 121 % and 115 % of their respective daily and flood averages.
Keywords: hydrology; civil engineering; hydrologic sciences